Amelia Bedelia Shapes Up - Parish, Herman; Avril, Lynne 1951- (New York, NY : Greenwillow Books, an imprint of HarperCollinsPublishers, 2014)
Picked last for kickball, Amelia Bedelia gets another chance to prove her athleticism when her class holds a mini-Oylympics.
Keywords: Sports -- Fiction; Schools -- Fiction; Humorous Stories